2019
DOI: 10.1021/acsami.9b06372
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriorhodopsin Enhances Efficiency of Perovskite Solar Cells

Abstract: In recent years, halide perovskites have upstaged decades of development in solar cells by reaching power conversion efficiencies that surpasses polycrystalline silicon performance. The efficiency improvement in the perovskite cells is related to repeated recycling between photons and electron-hole pairs, reduced recombination losses and increased carrier lifetimes. Here, we demonstrate a novel approach towards enhancing the efficiency of perovskite solar cells by invoking the Forster Resonance Energy Transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Proteins: Das et al recently reported on how to enhance PSC's efficiencies through protein functionalization of the TiO 2 electrode. [362] In particular, the bacteriorhodopsin (bR) protein was immobilized on the TiO 2 surface by covalent attachment of the protein via cysteine groups. The bR molecules between TiO 2 and the perovskite layers have a key role in enhancing the photon absorption and hot carrier transfer, as the transfer of photogenerated electrons from the perovskite absorber to bR molecules through the Forster resonance energy transfer (FRET) process.…”
Section: Charge Transport Layermentioning
confidence: 99%
“…Proteins: Das et al recently reported on how to enhance PSC's efficiencies through protein functionalization of the TiO 2 electrode. [362] In particular, the bacteriorhodopsin (bR) protein was immobilized on the TiO 2 surface by covalent attachment of the protein via cysteine groups. The bR molecules between TiO 2 and the perovskite layers have a key role in enhancing the photon absorption and hot carrier transfer, as the transfer of photogenerated electrons from the perovskite absorber to bR molecules through the Forster resonance energy transfer (FRET) process.…”
Section: Charge Transport Layermentioning
confidence: 99%
“…In such applications, the visible light absorption (λmax = 568 nm) and good photochemical stability of the bound retinal cofactor make bR a good photosensitizer. Recently, the incorporation of bR in a methylammonium lead(II) iodide (MAPbI3) based perovskite solar cell improved the overall energy conversion compared to the same architecture without bR, with performance gain attributed to a decreased charge carrier recombination in the photoactive layer [140]. Such applications do not directly utilize the light induced proton release activity of bR, though some researchers have taken advantage of this to produce photoelectrochemical devices for generating transient photocurrents induced by changes in the local proton concentrations, of interest in the biosensors and wearable devices fields [141,142].…”
Section: Bacteriorhodopsin As a Catalyst To Improve Device Performancesmentioning
confidence: 99%
“…Both protein–pigment complexes have shown remarkable thermal stability and their structural, biochemical, and photophysical properties have been extensively studied [ 15 , 16 ]. Similarly, both PSI and bR have also been widely used in a variety of biotechnological applications, most notably in BSSCs [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%